MEDAN MAKNA VERBA GERAKAN KAKI DALAM BAHASA MELAYU DIALEK SAMBAS - Emi Kiki Harianti; Sisilya Saman Madeten; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract.Sentebang village is one area in Sambas Regency, of which the Sambas Dialect of Malay language (BMDS) emerged and developed. Used in daily language, BMDS functions as the means of communication between the community and as the identity of Sentebang village. This paper discusses the foot movement verbs in BMDS including the lexemes, components, lexical meanings, and semantic functions of leg movements. This study aims to describe the foot verbs in BMDS based on the problems. The output of this study is as the material for comparison to other languages and as language preservation and insights for readers. The findings discovered 34 lexemes of foot verbs, in the form of leg movements, 8 lexemes using soles of the feet, 2 lexemes using the heel, 2 lexemes using instruments, 2 lexemes of leg movements using the help of hands, 2 lexemes using off footing, 2 lexemes of leg movements using airing and landing feet, 2 lexemes using fingertips, 2 lexemes by sitting cross-legged, 3 lexemes by knee-folding, 3 lexemes by legs-folding, 4 lexemes by rests on one leg, 1 lexeme by using a bicycle, and 1 lexemes by using paddy instrument.  Keywords: Foot verbs, Sambas Dialect Malay Language